2-[(E)-2-(4-Chlorophenyl)ethenyl]-1-methylpyridinium 4-chlorobenzenesulfonate - Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title salt, C(14)H(13)ClN(+)·C(6)H(4)ClO(3)S(−), the cation exists in an E configuration with respect to the ethynyl bond and is approximately planar, with a dihedral angle of 3.4 (2)° between the pyridinium and benzene rings. The anion is approximately perpendicular to the cation plane, the benzene ring of the anion making dihedral angles of 89.4 (2) and 89.9 (2)°, respectively, with the pyridinium and benzene rings of the cation. In the crystal structure, the cations are linked into a chain along the c axis by C—H⋯Cl interactions. The anions are linked to the adjacent cation chains by C—H⋯O and C—H⋯Cl interactions, forming a two-dimensional network parallel to the bc plane. The crystal structure is further stabilized by C—H⋯π interactions. A π–π interaction is also observed between the pyridinium ring and the benzene ring of the cation with a centroid–centroid distance of 3.668 (3) Å.